Ethical behavior in business: A hierarchical approach from the talmud - Friedman, Hershey H. (Journal of business ethics, 1985)
The Talmud, the compilation of Jewish oral law, is over 1500 years old and includes extensive discussions of business ethics. This paper presents four levels of ethical behavior in business gleaned from the words of the Talmud. At the lowest level, an individual is just barely inside the law; the highest level is “the way of the pious”. The author has attempted to relate the ethics in ancient business situations to business practices today.